Environmentally Responsible Behavior: The Roles of Personal Norms, Perceived Value, and Destination Social Responsibility - Ginting, Ginta; Dewi, Ike Janita; Maesaroh, Imas (Universitas Mercu Buana, 2024)
Objective: The objective of the study is to analyze the factors that shape tourists' environmentally responsible behavior. The proposed research model integrates norm activation theory, stakeholder theory, and a utilitarian perspective. From the norm activation theory perspective, two variables, namely awareness of consequences and ascribed responsibility, are included in the model as antecedents of personal norms. Destination social responsibility, as a stakeholder effort to promote environmental protection, can strengthen the influence of personal norms on environmentally responsible behavior. Furthermore, the utilitarian perspective in the form of perceived value, which is the benefit that tourists obtain from traveling to a destination, is also a moderating influence of personal norms on environmentally responsible behavior. Methodology: This study involved 255 respondents who had visited Yogyakarta. Data were processed using Smart-PLS to determine the relationships between variables. Finding: The results show that awareness of consequences and ascribed responsibility are factors in forming personal norms. Personal norms have a positive influence on environmentally responsible behavior. Furthermore, the data supported the role of perceived value as a moderator. However, destination social responsibility does not moderate the influence of personal norms on environmentally responsible behavior. Conclusion: The study concludes that the norms activation theory holds that personal norms are antecedents to environmentally responsible behavior. Personal norms’s influence on environmentally responsible behavior is strengthened by perceived value.